Rural Area Development By Understanding Basic Infrastructure Needs Through Local Survey In Sibu, Sarawak - Tiffany, Ting Feng Nee (Universiti Sains Malaysia, 2017)
In Malaysia, there are still issues circulating the inadequate rural basic infrastructure. In many parts of Sabah and Sarawak, there are still lacking in connectivity and have limited coverage of water and electricity supply. The research area is set at 3 locations in Sibu, Sarawak. Sibu Town is the most populated and developed location among the 3, Sibu Jaya which is a new township on the outskirts of Sibu Town and last but not least, Selangau District, a small town that focuses on agriculture. The two objective of this research are: to understand and compare the basic infrastructure condition and infrastructure accessibility in Sibu; to analyse and suggest infrastructure improvements based on local perspective in Sibu. Data analysis was done by using descriptive analysis, Pearson’s Correlation Analysis and Multivariate Analysis of Variance (MANOVA). The research results can also be taken into consideration by policymakers or future researchers who are keen to know local perspective on infrastructure. The results highlight solving Sibu Town’s low public transportation access by utilizing the local’s advance technology connectivity to bus schedules and locations, solve Sibu Jaya’s dissatisfaction of public transport and high amount spent on travel by improving comfort and conditions of the public transport. Lastly, for Selangau, to start improving basic amenities, rural roads and rural to city connecting roads.